Mineral nutrient contents of some potato accessions of USA and Bangladesh - Mahamud, MA; Chowdhury, MAH; Rahim, MA; Mohiuddin, KM (Journal of the Bangladesh Agricultural University, 2016)
Twenty two potato accessions from USA were evaluated for nutrient contents. Two Bangladeshi varieties were also included for comparison. Nutritional analyses were performed in the Department of Agricultural Chemistry, BAU during November, 2014 to April, 2015. Considering macro nutrient content, the highest values of N, P, K and S were found in the accession AC 10062 whereas Ca and Mg contents were found highest in Bangladeshi variety Cardinal and USA accessions AC 10073, respectively. In case of micro nutrient, the maximum amounts of Cu, Mn, B and Zn were observed in accession AC 10110, AC 10069, AC 10073 and AC 10109, respectively. Significant positive correlations were observed between N-P, N-K and K-Mn contents while K-Mg, Mn-B and Cu-B contents were negatively correlated. Considering all the parameters studied, the USA accession AC 10062, AC 10069 and AC 10110 were nutritionally superior to Bangladeshi variety Diamant and Cardinal. The accession AC 10062 was found as the best USA accession to produce nutrient rich potato in Bangladesh. J. Bangladesh Agril. Univ. 13(2): 207-214, December 2015